2012
DOI: 10.1590/s1516-35982012000500017
|View full text |Cite
|
Sign up to set email alerts
|

Digestible tryptophan requirements of meat quails in the growth phase

Abstract: -The objective of this experiment was to estimate the digestible tryptophan (DTrp) requirements for growing meat quails. In the first experiment (1-14 days of age), 1,950 quails were distributed in a completely randomized design, with six levels of DTrp (0.27; 0.30; 0.33; 0.36; 0.39 and 0.42% of diet), five replications and 65 quails per experimental unit.There was a linear increase of feed intake, tryptophan intake, weight gain and body weight with the DTrp levels increase. In the second experiment (15-35 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…(2012) found no differences for meat cuts of male laying quail linings fed with energy levels between 2600 to 3000 kcal/kg, for dry matter, crude protein and mineral matter. However, these authors observed differences in the ether extract content, as well as Ton et al (2011) who reported an increase in the content of ether extract, with an increase in the levels of metabolizable energy (2800−3100 kcal/kg), which did not occur in this study.…”
Section: Vasconcelos Et Al (2014) Evaluated the Carcass Characteristi...contrasting
confidence: 86%
See 2 more Smart Citations
“…(2012) found no differences for meat cuts of male laying quail linings fed with energy levels between 2600 to 3000 kcal/kg, for dry matter, crude protein and mineral matter. However, these authors observed differences in the ether extract content, as well as Ton et al (2011) who reported an increase in the content of ether extract, with an increase in the levels of metabolizable energy (2800−3100 kcal/kg), which did not occur in this study.…”
Section: Vasconcelos Et Al (2014) Evaluated the Carcass Characteristi...contrasting
confidence: 86%
“…Although, breast yield was affected by the level of ME, indicating that the increase in the levels of ME in the diet provided a reduction in breast yield, with greater deposition of fat in the muscle and its loss in the evisceration process. According to Griep Júnior et al (2017), surplus energy is stored as fat in the carcass, mainly in the breast.Although birds deposit more fat on the ends of the muscle pectoralis major and in the viscera, part of this fat is also directed to the deposition between muscle fibres, important for meat tenderness, as reported in the texture analysis Ton et al (2011). found no significant effect of the metabolizable energy in relation to the weight and yield of the breast in beef quails in the 4-to-35-day phase fed with different energy levels (2800, 2900, 3000, 3100 kcal/kg of feed).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Trp also contributes as a precursor to the production of the co-enzyme nicotinamide adenine dinucleotide and its phosphorylated form, which are induced to recycle antioxidant enzymes such as glutathione peroxidase and catalase (Agledal et al, 2010;Sainio et al, 1996;Xiao et al, 2018). In addition, the meat yield and dressing percentage increase with the added Trp levels (Corzo et al, 2005;Denbow et al, 1993;Kerr et al, 2005;Khanipour et al, 2019;Wei et al, 2011), possibly due to enhanced protein deposition (Fatufe et al, 2005;Ton et al, 2012) as a consequence of the stimulated secretion of insulin-like growth factor Ι. Insulin-like growth factor Ι promotes the utilization of amino acids and glucose, thereby leading to enhanced protein anabolism and reduced protein degradation via downregulation of the mRNA expression levels of cathepsin B and 20S protease (Duclos et al, 1993;McMurtry, 1998;Pan et al, 2013). Corticosterone suppresses protein synthesis and increases the breakdown of proteins (Dong et al, 2007;Hayashi et al, 1994).…”
Section: Tryp Tophan and Me At Qualit Y Fe Atu R E Smentioning
confidence: 99%
“…methionine + cysteine, threonine and tryptophan for meat-type quails from 15 to 35 d of age have been widely studied (Scherer et al, 2009;Ton et al, 2012;Ton et al, 2013;Ribeiro, 2015). Valine is considered the 4 th limiting amino acid in corn and soybean meal-based diets for broilers (Corzo et al, 2007;Rostagno et al, 2011).…”
Section: Introductionmentioning
confidence: 99%